Feasibility and safety of endoscopic resection for duodenal gastrointestinal stromal tumors - Shaobin Luo; Zu-Qiang Liu; Li Wang; Yi-Qun Zhang; Ming-Yan Cai; Quan-Lin Li; Ping-Hong Zhou (Endoscopy International Open)
Background: Endoscopic resection for duodenal gastrointestinal stromal tumors (GISTs) is still considered a great challenge with a high risk of complications. This study aimed to evaluate the effectiveness and safety of endoscopic resection for duodenal GIST.